Skrining Senyawa Antibakteri dari Minyak Atsiri Rimpang Temu Kunci (Boesenbergia pandurata) terhadap Staphylococcus aureus dengan Metode Bioautografi Kontak - Christiana, Indah; Soegianto, Lisa (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2020)
Fingerroot are generally used as a remedy for rheumatism, gastroenteritis, mucositis, diuretic, malaria, bowel disorders, flatulence, skin diseases, diarrhea, mouth sores, and intestinal worms. Essential oils found in Fingerroot are generally used as antibacterial. The purpose of this study is to determine the antibacterial activity of Fingerroot essential oils against Staphylococcus aureus and to determine the antibacterial compound of Fingerroot essential oils (Boesenbergia pandurata) using contact biautography methods. Fingerroot essential oil was obtained by the Stahl distillation method. Determination of the class of efficacious compounds was carried out by contact bioautography method and anisaldehyde-sulfuric acid and vanillin sulfate were used as spray reagent. The Fingerroot essential oil yields 0.38% and monoterpenes was determined as an antibacterial agent against Staphylococcus aureus.